A novel pre‐emergence herbicide (Diclosulam) as an environmentally friendly weed management option in peanut and its phytotoxicity evaluation. Issue 1 (15th February 2021) - Meena, Har N.; Yadav, Ranjeet S.; Jain, Navin K.; Yadav, Mayank
Abstract: A two‐season field experiment was conducted to evaluate the efficacy of diclosulam compared with recommended doses of pendimethalin and oxyfluorfen for weed management in peanut. Persistence of diclosulam in oil, de‐oiled cake, haulm of peanut, and soil was also studied. Diclosulam 22 and 26 g a.i. ha −1, and a weed‐free check had a high pod yield due to more mature pods and their mass. Pre‐emergence application of diclosulam 26 g a.i. ha −1 provided better weed management and enhanced peanut growth and yield with high net returns. Phytotoxicity studies indicated that the diclosulam application did not cause any phytotoxic symptoms (vein clearing, epinasty, hyponasty, wilting, and injury) on leaf tips and leaf surface of peanut. Diclosulam residues in peanut viz. oil, de‐oiled cake, haulm, and soil were below the detection level after harvesting of peanut from the experimental field. Further, germination percentage and seed cotton yield of cotton crop cultivated after peanut were also not affected significantly.